The Death of Semar - John Giordano (Respons: Jurnal Etika Sosial, 2015)
Melalui artikel ini penulis menelaah peran memori kultural pada masainterkoneksi global sekarang ini. Penulis mensinyalir bahwa gagasan tradisionaltentang budaya terancam oleh “industri budaya” seperti teknologi informasi danmedia masa. Di Dunia Barat, fungsi budaya sebagai mesin perubahan dan reformasitampak tergerus oleh industri tersebut. Tapi di Asia Tenggara – khususnya Indonesia– kekuatan eksternal serta upaya internal untuk mempertahankan identitas budayalokal tetap terjaga agar berimbang. Isu ini diteropong berdasarkan perpektif Michelde Certeau. Gagasan ini ditampilkan melalui telaah kisah “kematian Semar” dalamWayang. Kesadaran akan keberimbangan antara pengaruh eksternal dan pemeliharaanbudaya internal itu sangatlah penting di dalam menyikapi jaringan kekuatan globalyang memaksakan masuknya berbagai struktur religius, politik, kekuangan danhukum ke dalam budaya Indonesia. This essay will examine the role of cultural memory in an age of globalinterconnection. It will discuss how the traditional idea of culture is threatened by the “culture industry,” information technology and the media. In the West, there seemsto be a loss of culture’s function as an engine of change and reform. But throughoutthe history of South East Asia (and especially in Indonesia) one sees a both a processof appropriation of ideas from the outside, and at the same time, the maintenance ofa deeper cultural identity that is resistant to complete control. It is an unconsciousmemory – or a cultural reflex – present within the languages and stories and rationalities.I will explain this with reading of Michel de Certeau . And I will show how the Wayangstory of the “Death of Semar” is emblematic of this idea. The awareness of these oldprocesses of appropriation and resistance are extremely important in our age of globalnetworks of power that attempt to impose, various religious, political, financial andlegal structures.